ANALYSIS OF THE ROLE OF PHYSICAL EDUCATION, SPORTS AND HEALTH IN CHARACTER FORMATION AT THE HIGH SCHOOL LEVEL (INTERNATIONAL SEMINAR, 2025)
Personality is a mixture of characters and characters are different from one another. The concept of a good personality with the right attitude and the right attitude in bonding with others as well as bonding in oneself. Physical activities make the development of the body more perfect. Exercise and physical learning must be developed by a pedagogical system and a practical system, both of which have stages ranging from cognitive or lower, intermediate and advanced or large classes. Personality development must be formed for a long time and is better to start from childhood. Exercise psychology and exercise philosophy are aspects that support personality building. Physical Learning of Exercise and Health makes students become good personalities, because a person is obliged to obey the provisions of the regulations, and develop them into a responsibility that leads to maturity.